Ming‐Phos/Gold(I)‐Catalyzed Stereodivergent Synthesis of Highly Substituted Furo[3, 4‐d][1, 2]oxazines†. Issue 6 (13th April 2020) - Zhou, Lujia; Xu, Bing; Ji, Danting; Zhang, Zhan‐Ming; Zhang, Junliang
Summary of main observation and conclusion: A gold(I)‐catalyzed asymmetric intermolecular tandem [3+3]‐cyclization reaction of 2‐(1‐alkynyl)‐2‐ alken‐1‐ones with nitrones has been developed by using Ming‐Phos as a chiral ligand. This method enables access to the stereodivergent synthesis of highly substituted furo[3, 4‐ d ][1, 2]oxazines in excellent efficiency and stereoselectivity (up to 99% yield, 99% ee, >20 : 1 dr). Abstract : A highly enantioselective gold‐catalyzed intermolecular [3+2] cycloaddition of 2‐(1‐alkynyl)‐2‐ alken‐1‐ones with nitrones was realized by the application of Ming‐Phos M5 or M3 as chiral ligands. Both enantiomers of the cycloadducts with opposite configuration could be obtained in high yields with high regio‐ and enantioselectivity by the employment of either diastereomer of the chiral ligands.